Epidemiological Risks: Importance when Zoning Administrative Territories and Activating the Epidemic Process during Infectious Diseases - E. G. Yanovich; E. A. Moskvitina (Эпидемиология и вакцинопрофилактика, 2020)
Along with the theoretical concepts and definitions of risk adopted in the epidemiological analysis of infectious diseases, the identification of «risk areas» is of great importance.The aim is to show the role of risk factors when determining the «risk areas» and in the genesis of complications of the epidemiological situation. Taking into account the multifactorial nature of the epidemic process under infectious diseases, we describe the risks used in zoning of natural focal particularly dangerous (plague, tularemia, anthrax, Ebola virus disease, Yellow fever); arbovirus (Crimean-Congo haemorrhagic fever, West Nile Fever and anthroponotic (cholera and other acute enteric infection (AEI) of norovirus, rotavirus and enterovirus etiology) infections. The importance of risk factors and conditions for their implementation in AEI with water pathogen distribution (unsatisfactory state of water supply and water use, population migration, etc.) and emergencies, in which certain risk factors can contribute to the complication of the epidemic situation, is shown.Conclusion. The use of risk factors in zoning of administrative territories is aimed at improving epidemiological surveillance. It is possible that potential risk factors can transfer to real, what results in activation of the epidemic process.